A Study on Nexus Between Renewable Energy and Fossil Fuel Consumption in Commercial Sectors of United States Using Wavelet Coherence and Quantile-on-Quantile Regression - Singh, Sanjeet; Bansal, Pooja; Bhardwaj, Nav (Frontiers in Energy Research, 2022)
The inertia of fossil fuels in the commercial sector of the United States has maintained its momentum throughout, and efforts to replace it with renewable energy has continuously been made. This dynamic relationship is impacted by multi-economic and political variables both in the domestic and international markets. In this paper, we have explored the dynamic impact of total renewable energy consumption (RE) on the decomposed wavelet frequencies of energy consumed by fossil fuels (FE) in the commercial sectors of the United States economy. In particular, we have applied wavelet coherence and quantile-on-quantile regression methodologies to evaluate this relationship. The monthly data from the US Energy Information Administration over a period of January 2001 to July 2021 was procured for the present study. Our empirical findings based on wavelet coherence showed significant co-movements between FE and RE with positive association in short-run while negative association in long-run monthly frequency bands. For our five models based on quantiles and decomposed wavelet frequencies of FE, four models show that renewable energy consumption has an antagonistic relation with the FE in the commercial sector of the United States.